British Heart Rhythm Society Clinical Practice Guidelines on the Management of Patients Developing QT Prolongation on Antipsychotic Medication. Issue 3 (2019) - Lambiase, Pier D; Bono, Joseph Paul de; Schilling, Richard J; Lowe, Martin; Turley, Andrew; Slade, Alistair; Collinson, Jason; Rajappan, Kim; Harris, Stuart; Collison, Jason; Carpenter, Viki; Daw, Holly; et al.
No abstract available